Urea recycling in beef cattle fed prairie hay- based diets - Bailey, E.A.; Brake, D.W.; Anderson, David E.; Jones, M.L.; Titgemeyer, Evan C.; Olson, K. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Maximizing utilization of native rangeland is an important aspect of the cow/calf phase of beef production. Native rangeland is often of poor quality (less than 7% crude protein). Protein content of the rangeland is important because nitrogen is a key growth factor used by ruminal microbes. Without adequate nitrogen, the ruminal ecosystem will not operate at peak efficiency, which subsequently reduces the supply of nutrients to the animal. Historically, producers have provided supplemental nutrients to their cattle to achieve maximum performance. Both supplemental protein and energy have been provided to cattle consuming low-quality forage with varying levels of success. Typically, supplemental energy without adequate protein reduces fiber digestion by cattle. On the other hand, supplemental protein consistently improves overall performance.
Keywords: Beef; Prairie hay; Protein; Performance